Indigenous knowledge in climate adaptation planning: reflections from initial efforts - Ciocco, Tony W.; Miller, Brian W.; Tangen, Stefan; Crausbay, Shelley D.; Oldfather, Meagan F.; Bamzai-Dodson, Aparna (Frontiers in Climate, 2024)
There are increasing calls to incorporate indigenous knowledge (IK) into climate adaptation planning (CAP) and related projects. However, given unique attributes of IK and the positionality of tribal communities to scientific research, several considerations are important to ensure CAP efforts with IK are ethical and effective. While such topics have been thoroughly explored conceptually, incorporation of IK into CAP is a nascent field only beginning to report findings and improve science production and delivery. Based on recent work with Ute Mountain Ute (UMU) resource managers and knowledge holders, we reflect on key considerations for incorporating IK into CAP: the importance of sustained and multi-level tribal engagement, operational approaches to IK incorporation, cross-cultural challenges with risk-based approaches, and how CAP can support existing tribal priorities. We hope exploring these considerations can help set appropriate expectations, promote ethical interactions, and increase the effectiveness of tribal CAP and related efforts.